2021
DOI: 10.14710/jp.20.2.178-186
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Loneliness and Self-Compassion as Predictors of Depressive Symptoms in College Students

Abstract: High prevalence of depressive symptoms was found in college students. Loneliness, as one common problem incollege students, is assumed to have a role in the development of depressive symptoms. Earlier research foundself-compassion to be associated with better mental health. It is necessary to examine how loneliness and self-compassion play a role in the presence of depressive symptoms in college students. A total of 401 college studentsin the Jabodetabek area were involved in this research by completing online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The analysis focused on research conducted on Indonesian participants. The results of the analysis obtained by the researcher are described in the following table: Several research articles analyzed illustrate that self-compassion correlates with several psychological variables including loneliness and depression (Ausie & Poerwandari, 2021), mindfulness and depression (Fourianalistyawati et al, 2018), mindfulness and resilience (Salsabila & Widyasari, 2021), mental well-being and Irani Harefa, Edi Hamdi, Tantri Yanuar, Rina Annindita academic engagement (Kotera et al, 2022), and self-regulation (Sugianto, Anna, & Sutanto, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis focused on research conducted on Indonesian participants. The results of the analysis obtained by the researcher are described in the following table: Several research articles analyzed illustrate that self-compassion correlates with several psychological variables including loneliness and depression (Ausie & Poerwandari, 2021), mindfulness and depression (Fourianalistyawati et al, 2018), mindfulness and resilience (Salsabila & Widyasari, 2021), mental well-being and Irani Harefa, Edi Hamdi, Tantri Yanuar, Rina Annindita academic engagement (Kotera et al, 2022), and self-regulation (Sugianto, Anna, & Sutanto, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In Indonesian context, Shapero et al (2018) examined the role of self-compassion towards depression symptoms among college students in Surabaya and found that there is a significant role of self-compassion on depression symptoms among college students. A study from Ausie and Poerwandari (2021) illustrates the importance of considering the quality of self-compassion as an effort to reduce depression symptoms in college students. Maslita et al (2021) examined the effect of cognitive emotion regulation on depression in final year students in Indonesia showed that there was a significant influence between cognitive emotion regulation and depression.…”
mentioning
confidence: 99%